2010
DOI: 10.2478/v10032-010-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitration of Organic Materials on Nitrogen Availability and Yield of Tomato in Soilless Culture

Abstract: SummaryIn the cultivation of horticultural plants in greenhouses the most commonly used substrate is rockwool, while organic substrates are used in an unprocessed state. Cultivation in organic substrates, after they have been suitably processed, also makes it possible to obtain high yields at levels similar to those in rockwool cultures. Fibrous organic substrates, due to the wide C:N ratio, are characterized by high biological sorption towards nitrogen, causing N deficiency during the initial period of plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It seems that such filtrates could be used as fertilizer in horticulture, e.g., for soilless cultivation of vegetables in greenhouses on various types of growing media (e.g., Rockwood or Gordan-Master mineral wool). The content of fertilizing elements in filtrates from HNO3/KOH pulping of WS is higher or similar to the content of N−NO3 nitrogen and of K in the nutrient solution used in this type of crop for fertilizing tomatoes, amounting to 200 to 250 mg/dm 3 and 280 to 380 mg/dm 3 , respectively (Kaniszewski et al 2010) and the content of N-NO3, N-NH4, and K in the root zone of plants cultivated with this method, amounting to 400 to 600 mg/dm 3 , 0 to 60 mg/dm 3 , and 300 to 800 mg/dm 3 (Dyśko et al 2012).…”
Section: Resultsmentioning
confidence: 77%
“…It seems that such filtrates could be used as fertilizer in horticulture, e.g., for soilless cultivation of vegetables in greenhouses on various types of growing media (e.g., Rockwood or Gordan-Master mineral wool). The content of fertilizing elements in filtrates from HNO3/KOH pulping of WS is higher or similar to the content of N−NO3 nitrogen and of K in the nutrient solution used in this type of crop for fertilizing tomatoes, amounting to 200 to 250 mg/dm 3 and 280 to 380 mg/dm 3 , respectively (Kaniszewski et al 2010) and the content of N-NO3, N-NH4, and K in the root zone of plants cultivated with this method, amounting to 400 to 600 mg/dm 3 , 0 to 60 mg/dm 3 , and 300 to 800 mg/dm 3 (Dyśko et al 2012).…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, Vandcasttele et al [ 84 ] reported that reed straw, miscanthus straw, and flax shives have a comparatively high risk of N immobilization compared to peat. There are several strategies to overcome this N immobilization, such as the addition of N fertilizers, treatment with N-containing acid (HNO 3 ) [ 174 ], shifting the pH from the optimal range of microbes, etc. [ 84 ].…”
Section: Untransformed Agro-industrial Residues: Moving Forwardsmentioning
confidence: 99%
“…[ 84 ]. Also, nitration of plant fibers (saw dust, flax shives, rye straw) with nitric acid enhanced the availability of N [ 174 ].…”
Section: Untransformed Agro-industrial Residues: Moving Forwardsmentioning
confidence: 99%